The Arabidopsis RNA-Binding Protein AtRGGA Regulates Tolerance to Salt and Drought Stress. Issue 1 (17th March 2015) - Ambrosone, Alfredo; Batelli, Giorgia; Nurcato, Roberta; Aurilia, Vincenzo; Punzo, Paola; Bangarusamy, Dhinoth Kumar; Ruberti, Ida; Sassi, Massimiliano; Leone, Antonietta; Costa, Antonello; Grillo, Stefania
Abstract : An Arabidopsis RNA-binding protein contributes to drought and salt stress tolerance. Abstract: Salt and drought stress severely reduce plant growth and crop productivity worldwide. The identification of genes underlying stress response and tolerance is the subject of intense research in plant biology. Through microarray analyses, we previously identified in potato ( Solanum tuberosum ) StRGGA, coding for an Arginine Glycine Glycine (RGG) box-containing RNA-binding protein, whose expression was specifically induced in potato cell cultures gradually exposed to osmotic stress. Here, we show that the Arabidopsis ( Arabidopsis thaliana ) ortholog, AtRGGA, is a functional RNA-binding protein required for a proper response to osmotic stress. AtRGGA gene expression was up-regulated in seedlings after long-term exposure to abscisic acid (ABA ) and polyethylene glycol, while treatments with NaCl resulted in AtRGGA down-regulation. AtRGGA promoter analysis showed activity in several tissues, including stomata, the organs controlling transpiration. Fusion of AtRGGA with yellow fluorescent protein indicated that AtRGGA is localized in the cytoplasm and the cytoplasmic perinuclear region. In addition, the rgga knockout mutant was hypersensitive to ABA in root growth and survival tests and to salt stress during germination and at the vegetative stage. AtRGGA -overexpressing plants showed higher tolerance to ABA and salt stress on plates and in soil, accumulating lower levels of proline when exposed to drought stress. Finally, a global analysis of gene expression revealed extensive alterations in the transcriptome under salt stress, including several genes such as ASCORBATE PEROXIDASE2, GLUTATHIONE S-TRANSFERASE TAU9, and several SMALL AUXIN UPREGULATED RNA- like genes showing opposite expression behavior in transgenic and knockout plants. Taken together, our results reveal an important role of AtRGGA in the mechanisms of plant response and adaptation to stress.